Influenza vaccination of staff in aged care facilities in the ACT: how can we improve the uptake of influenza vaccine? - Linda Halliday; Jennifer A. Thomson; Leslee Roberts; Shirley Bowen; Cathy Mead (Elsevier, 2003)
Abstract Objective: To examine the self‐reported uptake of influenza vaccine by staff in residential aged care facilities in the Australian Capital Territory (ACT), and the factors influencing vaccine uptake by staff. Methods: Two confidential cross‐sectional surveys were conducted in all (n=19) residential aged care facilities in the ACT in June 2000. An interview with directors of each facility collected information on the institutional policy and practices for influenza vaccination. An anonymous postal survey of staff collected information on self‐reported influenza vaccination status and staff awareness and attitudes to the vaccination. Results: All directors were interviewed (n=19) and 50% of staff questionnaires (n=587) were completed. Of respondents, 28% reported receiving influenza vaccine for the 2000 influenza season. Uptake of the vaccine was associated with particular policies and practices of facilities such as: organisation of vaccination for staff (OR 2.52, CI 1.38-4.59, p<0.001); provision of reminders to staff (OR 2.73, CI 1.70-4.06, p<0.001); and provision of information on the need for vaccination (OR 1.94, CI 1.03-3.67, p<0.001). Other factors significantly associated with influenza vaccine uptake included: previous uptake of the vaccine (OR 52.2, CI 35.2-77.4, p<0.001), vaccination arranged by the workplace (OR 4.02, CI 2.66-6.07, p<0.001), and awareness of recommendations for staff employed in aged care facilities (OR 3.66, CI 2.28-5.85, p<0.001). The main reasons given for not receiving the vaccine were the belief that it had significant side effects (42%, n=146), and concerns about its effectiveness (32%, n=109). Conclusions: This study identified a number of factors that can be incorporated into strategies and programs to improve uptake of influenza vaccine by staff in residential aged care facilities.